Enhancing Elementary School Students' Reading Comprehension Skills Using the Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) Model based on Project-Based Learning (PjBL) - Milah, Neneng Hayatul; Damaianti, Vismaia S.; Mardiah, Dede (Mimbar Sekolah Dasar, 2025)
Reading comprehension is a crucial language skill for elementary school students in the 21st century. However, the quality of reading instruction in Indonesian schools remains inadequate. An assessment of fourth-grade narrative text comprehension found that only 30% of students answered questions effectively, while 70% struggled. This study aimed to evaluate the effectiveness of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) model, integrated with Project-Based Learning (PjBL), in improving reading comprehension among fourth-grade students in Cimahi, Indonesia. Using a one-group pretest-posttest design with 30 students as participants, the intervention was conducted over four sessions. The teacher implemented ARIAS through Project-Based Learning. Students created an explosion box project based on 5W+1H questions (Who, What, Where, When, Why, and How), targeting skills such as identifying main ideas, locating details, interpreting vocabulary, making inferences, and evaluating text structure. The pretest mean score was 62.70, rising to 77.10 on the posttest. A paired sample t-test showed a t-value of -14.133 with a significance level of 0.001, indicating significant improvement. These findings suggest that integrating ARIAS with PjBL fosters student engagement and enhances reading comprehension. The study offers insights for educators on using structured motivational strategies and hands-on projects to improve literacy skills in elementary students.